Correlation between Deep Venous Thrombosis and Inflammation in Patients after Implantation of Permanent Pacemaker - Jianxin MA; Lian CUI; Wenjin HUO; Guanghui WANG; Xin QUAN; Jinping ZHANG (Tehran University of Medical Sciences, 2020)
Background: The correlation between postoperative deep venous thrombosis (DVT) and inflammation in patients with permanent cardiac pacemaker implantation was analyzed. Methods: A total of 130 cases undergoing permanent pacemaker implantation in the 305 Hospital of Chinese PLA and Fuwai Hospital from May 2014 to February 2017 were selected. Of the 130 cases, 60 patients complicated with DVT were selected as the observation group, and the remaining 70 cases without complications of DVT were selected as the control group. The relationship and influence of various factors were explored. Results: The number of patients smoking and the number of subjects with DVT history in the observation group were higher than those in the control group. In the observation group, plasminogen activator inhibitor (PAI)-1: Ag, PAI-1: Ac, thrombin-activated fibrinolysis inhibitor (TAFI): Ag, and TAFI: Ac levels were higher than those in control group (P<0.05). The levels of inflammatory factors of the peripheral blood of the observation group were significantly higher than those of the control group (P<0.05). In the correlation analysis of serum inflammatory factors and coagulation factors, CRP, IL-6, IL-10 were positively correlated with PAI-1: Ag level. Age, BMI, smoking history, number of implanted electrodes, DVT history, duration of immobilization and inflammatory factor levels had independent predictive value on postoperative complicated DVT. Conclusion: The serum inflammatory factors are closely associated with postoperative DVT in patients implanted with permanent cardiac pacemaker, and the serum inflammatory factors are a good reference for the evaluation of DVT.